Desjudicialização da execução fiscal: a necessária quebra de um paradigma - Silveira, Artur Barbosa da (2021)
In most developed countries, the tax enforcement process takes place, wholly or predominantly, at the administrative level. In Brazil, in turn, the execution and collection of tax debt still maintains the need for the Judiciary to act as its main paradigm. Studies indicate that the rate of recovery of tax credits in our country is unsatisfactory, and it is urgent and necessary to break the paradigm of the judicialization of tax enforcement, whether from a legal, economic, ethical and humanitarian reasons. Overcoming this problem, however, encounters both legal and cultural obstacles. The protest of the active debt certificate and the inscription of the debtor's name on delinquent registrations are useful but insufficient methods to ensure the efficiency of the tax debt collection system. The present work presents some hypotheses aiming to contribute to the improvement of the collection of the active debt and the tax collection as a whole.